Home to Big Stone Gap : a novel - Trigiani, Adriana (Ballantine Books, 2007)
Nestled in the lush Blue Ridge Mountains of Virginia, the town of Big Stone Gap has been home to Ave Maria Mulligan MacChesney and her family for generations. She's been married to her beloved Jack for nearly twenty years, raised one child and buried another, and run a business that binds her community together, all while holding close her tight circle of family and friends. But with her daughter Etta, having flown the nest to Italy, Ave Maria has reached a turning point. When a friend's postcard arrives with the message "It's time to live your life for you," Ave Maria realizes that she must go in search of brand new dreams. But before she can put her foot on the path, her life is turned upside down.